2014
DOI: 10.1002/chem.201402680
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Exfoliated Transition‐Metal Dichalcogenides (MoS2, WS2, and WSe2) is Lower Than That of Graphene and its Analogues

Abstract: Studies involving transition-metal dichalcogenides (TMDs) have been around for many decades and in recent years, many were focused on using TMDs to synthesize inorganic analogues of carbon nanotubes, fullerene, as well as graphene and its derivatives with the ultimate aim of employing these materials into consumer products. In view of this rising trend, we investigated the cytotoxicity of three common exfoliated TMDs (exTMDs), namely MoS2 , WS2 , and WSe2 , and compared their toxicological effects with graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
281
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 377 publications
(297 citation statements)
references
References 55 publications
16
281
0
Order By: Relevance
“…By comparing our data with those reported for the widely used Group 6 TMDs (namely MoS 2 ,WS 2 ,and WSe 2 ) [63] under similarconditions (such as undergoing a2 4h treatment of materials with A549 cells), we found that the Group 5t ransition metal ditellurides are generally more toxic than the Group 6T MDs.H owevera n exception was observed in WSe 2 ,w here it is more toxic than the Group 5t ransition metal ditellurides, with only VTe 2 being more toxic than WSe 2 (Table 1).…”
Section: Comparison With Other Tmdssupporting
confidence: 51%
“…By comparing our data with those reported for the widely used Group 6 TMDs (namely MoS 2 ,WS 2 ,and WSe 2 ) [63] under similarconditions (such as undergoing a2 4h treatment of materials with A549 cells), we found that the Group 5t ransition metal ditellurides are generally more toxic than the Group 6T MDs.H owevera n exception was observed in WSe 2 ,w here it is more toxic than the Group 5t ransition metal ditellurides, with only VTe 2 being more toxic than WSe 2 (Table 1).…”
Section: Comparison With Other Tmdssupporting
confidence: 51%
“…For MoS 2 , it is relatively more biocompatible than GO when comparing their in vitro and in vivo toxicity, because MoS 2 is rather inactive to biomolecules. 80,81 Considered together, these findings signified the improved biocompatibility of MoS 2 /GO nanocomposites for potential biomedical applications. Figure 9 Pro-inflammatory responses elicited by diverse materials in J774A.1 cells.…”
Section: Preferential Lung Accumulation Of Mos 2 /Go Nanocompositesmentioning
confidence: 82%
“…At the in vitro level, it was found that the cytotoxicity of MoS 2 , WS 2 , and WSe 2 nanosheets appeared to be low to different cell lines 15, 18, 32, 33. On the other hand, in our previous reports about the use of polyethylene glycol (PEG) functionalized TMDCs for in vivo imaging and therapy applications, we have uncovered that PEGylated MoS 2 and WS 2 showed no appreciable acute toxicity to the treated mice at our tested dose 16, 20, 23, 34.…”
Section: Introductionmentioning
confidence: 99%